The Health Externalities of Downsizing - Alexander Ahammer; Dominik Grübl; Rudolf Winter-Ebmer (Institute of Labor Economics (IZA), 2020)
We show that downsizing has substantial externalities on the health of workers who remain in the firm. To this end, we study mass layoff (ML) survivors in Austria, using workers who survive a ML themselves, but a few years in the future, as a control group. Based on high-quality administrative data, we find evidence that downsizing has persistent effects on mental and physical health, and that these effects can be explained by workers fearing for their own jobs. We also show that health externalities due to downsizing imply non-negligible cost for firms, and that wage cuts may have similar effects.
Keywords: J63; I12; J23; 330; downsizing; mass layoffs; health; job insecurity